Ocular Manifestations of Systemic Lupus Erythematosus: A Review of the Literature - Palejwala, Neal V. (Hindawi Publishing Corporation, 2012)
About one-third of patients suffering from systemic lupus erythematosus have ocular manifestations. The most common manifestation is keratoconjunctivitis sicca. The most vision threatening are retinal vasculitis and optic neuritis/neuropathy. Prompt diagnosis and treatment of eye disease is paramount as they are often associated with high levels of systemic inflammation and end-organ damage. Initial management with high-dose oral or IV corticosteroids is often necessary. Multiple “steroid-sparing” treatment options exist with the most recently studied being biologic agents.